2017
DOI: 10.1016/j.genhosppsych.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential for primary care to serve as a mental health home for people with schizophrenia

Abstract: Objective Primary care-based medical homes could improve the coordination of mental health care for individuals with schizophrenia and comorbid chronic conditions. The objective of this paper is to examine whether persons with schizophrenia and comorbid chronic conditions engage in primary care regularly, such that primary care settings have the potential to serve as a mental health home. Method We examined the annual primary care and specialty mental health service utilization of adult North Carolina Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Fifth, we stratified analyses by enrollees residing in New York City (NYC) vs non-NYC (eTables 25 and 26 in Supplement 1), and, for patients with schizophrenia, we stratified by comorbidity score (eTable 27 in Supplement 1). 32 See the eMethods in Supplement 1 for more details. Analyses were conducted using Stata, version 15 (StataCorp LLC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, we stratified analyses by enrollees residing in New York City (NYC) vs non-NYC (eTables 25 and 26 in Supplement 1), and, for patients with schizophrenia, we stratified by comorbidity score (eTable 27 in Supplement 1). 32 See the eMethods in Supplement 1 for more details. Analyses were conducted using Stata, version 15 (StataCorp LLC).…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we stratified analyses by enrollees residing in New York City (NYC) vs non-NYC (eTables 25 and 26 in Supplement 1 ), and, for patients with schizophrenia, we stratified by comorbidity score (eTable 27 in Supplement 1 ). 32 …”
Section: Introductionmentioning
confidence: 99%
“…20 The PCMH model has been shown to improve some preventive screening and service use outcomes for people with SMI. [21][22][23][24] However, Bowdoin et al found that among people with mental illness, receiving care in a PCMH did not yield better preventive care or service use outcomes than having a non-PCMH usual source of care. 25,26 Enhancements to the PCMH model designed to meet the complex health needs of people with SMI may better leverage the potential of the model to serve this population, but evidence regarding what these enhancements should be is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Care delivery models have sought to better integrate delivery of behavioral and physical healthcare, but these models have faced challenges. Models such as Collaborative Care (20)(21)(22) or the Patient Centered Medical Home (23)(24)(25), where behavioral health is integrated into primary care settings, may have primary care providers (PCPs) who lack experience in treating individuals with SMI (24). In the Behavioral Health Home (BHH), where the coordination of care for physical healthcare is centered in the specialty mental healthcare setting (26,27), behavioral health providers may not feel equipped to address CVD risk factors (28).…”
Section: Introductionmentioning
confidence: 99%